Persistent infection due to a small-colony variant of Burkholderia pseudomallei leads to PD-1 upregulation on circulating immune cells and mononuclear infiltration in viscera of experimental BALB/c mice - See, J.X.; Chandramathi, S.; Abdulla, M.A.; Vadivelu, J.; Shankar, E.M. (Public Library of Science, 2017)
Background: Melioidosis is a neglected tropical disease endemic across South East Asia and Northern Australia. The etiological agent, Burkholderia pseudomallei (B.pseudomallei), is a Gram-negative, rod-shaped, motile bacterium residing in the soil and muddy water across endemic regions of the tropical world. The bacterium is known to cause persistent infections by remaining latent within host cells for prolonged duration. Reactivation of the recrudescent disease often occurs in elders whose immunity wanes. Moreover, recurrence rates in melioidosis patients can be up to ~13% despite appropriate antibiotic therapy, suggestive of bacterial persistence and inefficacy of antibiotic regimens. The mechanisms behind bacterial persistence in the host remain unclear, and hence understanding host immunity during persistent B. pseudomallei infections may help designing potential immunotherapy. Methodology/Principal findings: A persistent infection was generated using a small-colony variant (SCV) and a wild-type (WT) B. pseudomallei in BALB/c mice via intranasal administration. Infected mice that survived for >60 days were sacrificed. Lungs, livers, spleens, and peripheral blood mononuclear cells were harvested for experimental investigations. Histopathological changes of organs were observed in the infected mice, suggestive of successful establishment of persistent infections. Moreover, natural killer (NK) cell frequency was increased in SCV- and WT-infected mice. We observed programmed death-1 (PD-1) upregulation on B cells of SCV- and WT-infected mice. Interestingly, PD-1 upregulation was only observed on NK cells and monocytes of SCV-infected mice. In contrast, cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) downregulation was seen on NK cells of WT-infected mice, and on monocytes of SCV- and WT-infected mice. Conclusions/Significance: The SCV and the WT of B. pseudomallei distinctly upregulated PD-1 expression on B cells, NK cells, and monocytes to dampen host immunity, which likely facilitates bacterial persistence. PD-1/PD-L1 pathway appears to play an important role in the persistence of B. pseudomallei in the host.